(untitled) (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2024)
Background: Abruptio placenta refers to premature placental detachment from the uterus. Couvelaire uterus is a rare complication of abruptio placenta marked by blood infiltration of the myometrium following hemorrhage into the decidua basalis. This is a case of severe early-onset preeclampsia with rapid deterioration. Case presentation: A 35-year-old primigravida presented at 26 weeks 4 days with frontal headache and elevated blood pressure. On admission, with severe preeclampsia and type 1 fetal growth restriction, the patient received labetalol, nifedipine, magnesium sulfate, and antenatal steroids. After two days of hospitalization, she was discharged home to be closely monitored as an outpatient. She was readmitted with severe hypertension and developed abruptio placenta with fetal death. Following labor induction, the patient had significant antepartum hemorrhage necessitating an emergency hysterotomy. Intraoperatively, she had postpartum hemorrhage refractory to uterotonics with a Couvelaire uterus. Hemostasis was achieved using B-Lynch brace sutures. She developed hemolysis, elevated liver enzyme and low platelet count (HELLP) syndrome and acute kidney injury. She was transfused with packed red cells, fresh frozen plasma, and platelets. Hemodynamically unstable, she was admitted to the critical care unit and later stepped down to ward status and allowed home. Conclusion: Abruptio placenta is a clinical diagnosis, and a high index of suspicion is required because prompt action may be lifesaving. Complications such as Couvelaire uterus pose a significant challenge in management and may lead to hysterectomy. However, in select cases, the uterus can be preserved by applying B-lynch brace sutures.